2019
DOI: 10.1016/j.clinbiomech.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of healthy trapeziometacarpal cartilage properties using indentation testing and contrast-enhanced computed tomography

Abstract: Background: The trapeziometacarpal joint is a common site for osteoarthritis development in the hand. When osteoarthritis is present, it results in significant functional disabilities due to the broad range of activities performed by this joint. However, our understanding of osteoarthritis initiation and progression at this joint is limited because of the current lack of knowledge regarding the properties and structure of the corresponding cartilage layers. The objective of this study is to assess the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 40 publications
1
24
3
Order By: Relevance
“…In addition, there is consensus that cartilage degeneration of the first metacarpal originates and progresses from the volar area 4,10,30e32 . On the other hand, cartilage thinning in the trapezium is considered to volarly expand; however, this contradicts our findings 4,10,31 . These patterns were identified to have close relations to high load bearing in previous contact area studies 9,22,33e40 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, there is consensus that cartilage degeneration of the first metacarpal originates and progresses from the volar area 4,10,30e32 . On the other hand, cartilage thinning in the trapezium is considered to volarly expand; however, this contradicts our findings 4,10,31 . These patterns were identified to have close relations to high load bearing in previous contact area studies 9,22,33e40 .…”
Section: Discussioncontrasting
confidence: 99%
“…With aging, arthritis of the TMC joint progressively increases in prevalence, and a 91% prevalence has been reported in patients aged > 80 years 2 . Joint degeneration, concomitant with the progress of OA, results in the reduction of joint mobility, exacerbation of pain and swelling, weakness of grip and pinch, and overall disablement of the hand 3,4 . Reportedly, the pathophysiology of this disease is characterized by damage to the articular cartilage, osteophyte formation, changes in the subchondral bone, and synovitis 5 , and of these, the articular cartilage has garnered the most attention in relation to its pathogenesis, mainly because of its striking changes in advanced OA 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the distance between the two central articular points was increased to 1.5 mm for all specimens ( Figure 1 A). This value, which represents the modern human average thickness of cartilage in the TMC joint (both bones taken together), 64 was used as a proxy of intra-articular space between the bones. It should be clarified that our models assumed uniform cartilage thickness at joints, despite the fact that previous research has shown that this varies across the articular surface.…”
Section: Methodsmentioning
confidence: 99%
“…13 CECT studies demonstrate that cationic contrast agents accumulate throughout the bovine cartilage and are more sensitive to changes in the concentration of GAGs than anionic contrast agents. [14][15][16][17] Cationic agents are also successfully used to image ex vivo murine, 13,18 rabbit, 19 equine, 20,21 and human articular cartilage 22,23 as well as human menisci. 24 Additionally, CECT with CA4+ is used to image and characterize murine intervertebral disks.…”
mentioning
confidence: 99%